Non-sulfated cholecystokinin-8 reduces meal size and prolongs the intermeal interval in male Sprague Dawley rats - Dafalla, Amged I. (Neuropeptides, 2018)
The current study measured seven feeding responses by non-sulfated cholecystokinin-8 (NS CCK-8) in freely fed adult male Sprague Dawley rats. The peptide (0, 0.5, 1, 3, 5 and 10nmol/kg) was given intraperitoneally (ip) prior to the onset of the dark cycle, and first meal size (MS), second meal size, intermeal interval (IMI) length, satiety ratio (SR = IMI/MS), latency to first meal, duration of first meal, number of meals and 24-hour food intake were measured. We found that NS CCK-8 (0.5 and 1.0nmol/kg) reduced MS, prolonged IMI length and increased SR during the dark cycle. Furthermore, the specific CCK-B receptor antagonist L365, 260 (1 mg/kg, ip) attenuated these responses. These results support a possible role for NS CCK-8 in regulating food intake.